The truth about the music business a grassroots business and legal guide - Moore, Steve 1962-; Gale Group (Boston, Mass. Thomson Course Technology, 2005)
Designed for aspiring or current employees in the music business who wish to learn more about the business and legal aspects of their trade. It covers pertinent business and legal information for many professional music careers, from artists, writers, and booking agents to studio managers and major label executives.
1. Entertainment Attorneys -- 2. Choosing a Business Structure -- 3. Making a Business Plan -- 4. Advertising, Marketing, Promotion, and Distribution -- 5. Useful Tips -- 6. Intellectual Property -- 7. Publishing -- 8. Digital Rights -- 9. Why Sign a Record Deal? -- 10. Making Demos versus Masters -- 11. Management - Ancillary Services -- 12. General Principles of Contracts -- 13. Negotiating -- 14. Questionable Practices -- 15. Collecting Your Money -- 16. If All Else Fails, Sue -- 17. Organizations -- 18. Music Conferences, Festivals, Trade Shows, and Seminars -- 19. Insurance -- 20. Wills, Trusts, and Estates.
Electronic reproduction.
Keywords: Music trade -- United States; Music trade -- Law and legislation -- United States; Electronic books